Islamic Education in the Digital Era: Integrating Faith, Knowledge, and 21st-Century Skills - Syafrul Nalus; Onrico Candra; Linda Suanti; Rahmat Rahmat; Mardiah Binti Yahaya (AT-TA'LIM, 2024)
The rapid advancement of digital technology and increasing global interconnectedness have significantly transformed the landscape of education, posing new challenges for Islamic education to remain pedagogically relevant, epistemologically grounded, and socially transformative. In response to these challenges, this article aims to examine strategic approaches within Islamic education for integrating three essential pillars—faith, general knowledge, and 21st-century skills—into a relevant and responsive curriculum suited to the demands of the digital era. This study employs a qualitative theoretical analysis to examine curriculum integration strategies in Islamic education, using Constructivist Learning Theory and Integrated Curriculum Theory as analytical frameworks. These conceptual frameworks provide the basis for exploring how educational practices can move beyond fragmented content delivery toward cohesive and value-driven learning experiences. The study reveals that the digital age presents both challenges and opportunities for Islamic education. While it demands adaptability and technological fluency, it also provides a platform to reaffirm the ethical and spiritual dimensions of learning. In this context, strategies such as experiential learning, problem-based inquiry, and project-based instruction are essential for cultivating critical thinking, creativity, collaboration, communication, and contextual awareness among students. The findings suggest that integrating faith and knowledge empowers learners not only to attain academic excellence but also to internalize moral and spiritual values that guide behavior and decision making. A curriculum that is holistic, contextually relevant, and transformative is thus imperative in preparing a generation of Muslims who are not only intellectually competent but also spiritually resilient and socially responsible in navigating the complexities of modern life